Transforming Growth Factor β and Insulin Signal Changes in Stromal Fibroblasts of Individual Keratoconus Patients - Foster, James (Public Library of Science, 2014)
Keratoconus (KC) is a complex thinning disease of the cornea that often requires transplantation. The underlying pathogenic molecular changes in this disease are poorly understood. Earlier studies reported oxidative stress, metabolic dysfunctions and accelerated death of stromal keratocytes in keratoconus (KC) patients. Utilizing mass spectrometry we found reduced stromal extracellular matrix (ECM) proteins in KC, suggesting ECM-regulatory changes that may be due to altered TGFβ signals. Here we investigated properties of stromal cells from donor (DN) and KC corneas grown as fibroblasts in serum containing DMEM: F12 or in serum-free medium containing insulin, transferrin, selenium (ITS). Phosphorylation of SMAD2/3 of the canonical TGFβ pathway, was high in serum-starved DN and KC fibroblast protein extracts, but pSMAD1/5/8 low at base line, was induced within 30 minutes of TGFβ1 stimulation, more so in KC than DN, suggesting a novel TGFβ1-SMAD1/5/8 axis in the cornea, that may be altered in KC. The serine/threonine kinases AKT, known to regulate proliferation, survival and biosynthetic activities of cells, were poorly activated in KC fibroblasts in high glucose media. Concordantly, alcohol dehydrogenase 1 (ADH1), an indicator of increased glucose uptake and metabolism, was reduced in KC compared to DN fibroblasts. By contrast, in low glucose (5.5 mM, normoglycemic) serum-free DMEM and ITS, cell survival and pAKT levels were comparable in KC and DN cells. Therefore, high glucose combined with serum-deprivation presents some cellular stress difficult to overcome by the KC stromal cells. Our study provides molecular insights into AKT and TGFβ signal changes in KC, and a mechanism for functional studies of stromal cells from KC corneas.